Step-to-step spatiotemporal determinants of female sprint performance during the entire acceleration phase - Gleadhill, S.; Nagahara, R. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to clarify the kinematic determinants of maximal effort female sprint performance during the entire acceleration phase of a single sprint. Fifteen sub-elite female sprinters completed a 60 m maximal effort sprint from starting blocks over a long force platform system. Ground reaction force data was used to calculate step length, step frequency, support time and flight time. Pearson`s product moment correlation coefficient was used to clarify the association between the rate of changes in these spatiotemporal variables and acceleration at every step. Peformance determinants elucidated included the rate of changes in step length (1st to 10th steps), step frequency (2nd to 7th steps), support time (1st to 5th steps) and flight time (4th to 7th steps). Results were considered similar to past research on male sprinters, although showed slightly different correlations.